A comparative study between E‐neurons mathematical model and circuit model - M. Daliri; Pietro M. Ferreira; G. Klisnick; A. Benlarbi‐Delai (IET Circuits, Devices and Systems)
Abstract The basic concepts and techniques involved in the development and analysis of mathematical models for individual neurons are reviewed. A spiking neuron model uses differential equations to represent various neuronal activities that have more compatibility with circuit criteria and are chosen for developing a comparative study with circuit models. For this comparison, a new fully differential neuron that uses the fully differential aspects to reach more balanced differential equations to mathematical model is presented. This comparative study of the circuit model and a neuron mathematical model provides a quantitative understanding of the challenges between mathematical models and microelectronic circuit design criteria.